An analysis of product data management system development project - Tarsa, Janne (My University, 2016)
Companies whose core business is on manufacturing and selling of products efficient product data management system and the related processes are essential for success. Purpose of this study was to evaluate how re-engineering of product data management’s product processes and order-delivery processes and supporting IT systems succeed in a large company operating in manufacturing and services industry. These processes are the core business processes for the company. Secondary target was to give suggestions for further product data management system’s development based on the improvement are-as found in the analysis of the study material. Research problem and question were formed from the work assignment given by the company requesting the study. Based on the assignment study was decided to be con-ducted as a qualitative study. As the study concerned one company’s one business line case study approach was used. Theoretical framework was formed using literature re-view. Empirical material was collected using semi-structured interviews. Interviews were transcribed and coded. From coding emerged several themes which set frame for empirical material analysis. Analysis results were summarized and concluded to form suggestions and further research, validity and reliability of the study was also evaluated. The study was conducted as a case study in large Finnish company operating in the manufacturing and services business. Empirical data was collected in a semi-structured interview. Results revealed that development of the new product data management sys-tem and related processes were greatly needed and that the new system enabled more efficient way of working thus increasing the output of the product development and commercial processes. Future development needs identified were more tighter integra-tion to the other business support IT systems like manufacturing and enterprise resource planning and execution systems and sales support system.
Keywords: product data management system; enterprise resource planning system; fi=Ohjelmistotekniikka (DI)|en=Software Engineering|; fi=Tietotekniikan koulutusohjelma (DI)|